Alteration causes and processes in the stone material from the pavement in Baelo Claudia archeological site, Cadiz/Spain - M. Hoyos; S. Sánchez-Moral; J. C. Cañaveras; E. Sanz-Rubio (Materiales de Construccion, 1999)
A detailed study of the alteration causes in the stone material used in buildings and pavements from the ancient roman town of Baelo Claudia (Cádiz, South Spain) was carried out to establish their degree of conservation. Slabs from the pavement of the Forum showed in general a high and irreversible degree of degradation. In order to palliate the action of processes of degradation in subaerial conditions, in this work some measures are proposed to try to preserve the slabs in better conditions.